Say cheese--and die screaming! - Stine, R. L. (New York : Scholastic, 2009)
Julie discovers her camera is evil and is invited to Horrorland where she realizes the theme park is not all fun and games.
Say cheese--and die screaming! -- Enter HorrorLand -- Fear file.
4.6
5-8
Keywords: Amusement parks -- Juvenile fiction; Cameras -- Juvenile fiction; Amusement parks -- Fiction; Cameras -- Fiction; Horror stories; Amusement parks -- Fiction; Cameras -- Fiction; Horror fiction; Horror fiction